DOKTRIN MANUSIA UNIVERSAL DALAM ANTROPOLOGI METAFISIS SEYYED HOSSEIN NASAR - Mohammad Subhi (Jurnal Universitas Paramadina, 2014)
Insan kamil (perfect man) is perennial issue in sufism discourses. Systematically, Ibn Arabi introduced insan kamil doctrine, and Seyyed Hossein Nasr made its modern interpretation. Nasr used term universal man as  synonim of insan kamil. Hence, The article aims to elaborate arguments of universal man doctrine in Seyyed Hossein Nasr’s thought. As Ibn Arabi, point of view's Nasr is universal man has trhee aspects: cosmological, propetics,  and inisiatic. Whoever can be universal man trought path of spiritual knowledge.